The Dengvaxia Issue: Its Influence on Mothers’ Perception on Child Vaccination - Lun, Zen Sian; Dorado, Jan Lenard; Qian, Wang Xue; Mergal, Beryl Ben C.; Hernandez, Narcar (11th International Scholars Conference, 2018)
Dengue has been endemic in several countries worldwide. It is reported that millions are infected with the disease yearly, causing thousands of deaths. The Dengvaxia issue occurred when Sanofi Pasteur announced that the vaccine, which has been administered to grade-schoolers in the Philippines, can only be effective for those who have been previously infected with dengue. It has also been reported that the immunization program of the Philippines has been experiencing a decrease in the immunization rate. The study aimed to look into the influence of the Dengvaxia issue on mothers’ perceptions on child vaccination. This study employed a qualitative phenomenological research design. To recruit for participants, a purposive sampling method and snowball sampling methods were utilized to select 11 participants. A validated semi-structured questionnaire was used for the interview. Participants included mothers of children ages 0-24 months who have knowledge of the Dengvaxia issue. The data gathered were then analyzed using standardized methods. The findings of the study revealed that on the Dengvaxia issue, the themes were fear, empathy, and anger. On the mother’s perception towards vaccination, the themes were protection and giving up authority. Also, in terms of the influence of Dengvaxia Issue on child vaccination, identified themes were vaccine confidence and vaccine hesitancy. Furthermore, the study also revealed that nine out of the 11 mothers are still in favor of their children being vaccinated. It was therefore recommended that nurses must do continuous health education about the positive effects of immunizations in the community.